Rome in America : transnational Catholic ideology from the Risorgimento to fascism - D'Agostino, Peter R., 1962- (University of North Carolina Press, 2004)
For years, historians have argued that Catholicism in the United States stood decisively apart from papal politics in European society. Drawing on previously unexamined documents from Italian state collections and newly opened Vatican archives, Peter D'Agostino paints a starkly different portrait.